Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/cells9061556
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA Signature Associated to Interstitial Lung Abnormalities in Respiratory Asymptomatic Subjects

Abstract: Interstitial lung abnormalities (ILA) are observed in around 9% of older respiratory asymptomatic subjects, mainly smokers. Evidence suggests that ILA may precede the development of interstitial lung diseases and may evolve to progressive fibrosis. Identifying biomarkers of this subclinical status is relevant for early diagnosis and to predict outcome. We aimed to identify circulating microRNAs (miRNAs) associated to ILA in a cohort of respiratory asymptomatic subjects older than 60 years. We identified 81 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…Furthermore, a high TS rate in IPF patients <60 years old is considered a poor prognosis because these patients present with more nonspecific hematological and/or immunological abnormalities [ 64 ]. Although there is limited information regarding the role of circulating microRNAs in the induction of TS and its link with the regulation of senescence in lung diseases, a recent report suggests that the upregulation of circulating microRNAs is associated with the regulation of critical signaling pathways, including senescence, which is in agreement with a previous report that indicated that miR-34a regulates c-Myc and FoxM1; interestingly, both molecules have a role in hTERT transcription [ 119 , 120 ].…”
Section: Influence Of Immune Cells With Shorter Telomeres On Development Of Lung Diseasessupporting
confidence: 84%
“…Furthermore, a high TS rate in IPF patients <60 years old is considered a poor prognosis because these patients present with more nonspecific hematological and/or immunological abnormalities [ 64 ]. Although there is limited information regarding the role of circulating microRNAs in the induction of TS and its link with the regulation of senescence in lung diseases, a recent report suggests that the upregulation of circulating microRNAs is associated with the regulation of critical signaling pathways, including senescence, which is in agreement with a previous report that indicated that miR-34a regulates c-Myc and FoxM1; interestingly, both molecules have a role in hTERT transcription [ 119 , 120 ].…”
Section: Influence Of Immune Cells With Shorter Telomeres On Development Of Lung Diseasessupporting
confidence: 84%
“…2E). These selected miRNAs have also been shown to be expressed in lung tissue and serum from individuals with IPF (Casanova et al, 2021; Omote & Sauler, 2020; Ortiz-Quintero et al, 2020). These data suggest that composition of urine exosomes from individuals with IPF is the same as the composition from serum-derived exosomes in the same individual.…”
Section: Resultsmentioning
confidence: 99%
“…Among other possible biomarkers, the adhesion molecule sICAM-1 has been associated with ILA [ 41 ] as well as pro-inflammatory molecule resistin [ 17 ]. Additionally, leptin and the metabolites phosphatidylcholine, phosphatidic acid, betaine aldehyde, phosphatidylethanolamine, and 1-acylglycerophosphocholine [ 42–44 ] have been linked with ILA and certain microRNAs, in particular miR-193a-5p and miR–502–5p, have been shown to be upregulated in ILA and suggested as ILA biomarkers [ 45 ]. Rheumatoid arthritis (RA) related autoantibodies and anti-cyclic citrullinated peptide have been associated with ILA among smokers and rheumatoid factor IgA are associated with ILA regardless of smoking history [ 46 ].…”
Section: Epidemiological Associations and Parallels With Interstitial Lung Diseasementioning
confidence: 99%